RNA Pol III promoters—key players in precisely targeted plant genome editing - Kor, Sakshi Dharmendra; Chowdhury, Naimisha; Keot, Ajay Kumar; Yogendra, Kalenahalli; Chikkaputtaiah, Channakeshavaiah; Sudhakar Reddy, Palakolanu (Frontiers in genetics, 2023)
The clustered regularly interspaced short palindrome repeat (CRISPR)/CRISPR-associated protein Cas) system is a powerful and highly precise gene-editing tool in basic and applied research for crop improvement programs. CRISPR/Cas tool is being extensively used in plants to improve crop yield, quality, and nutritional value and make them tolerant to environmental stresses. CRISPR/Cas system consists of a Cas protein with DNA endonuclease activity and one CRISPR RNA transcript that is processed to form one or several short guide RNAs that direct Cas9 to the target DNA sequence. The expression levels of Cas proteins and gRNAs significantly influence the editing efficiency of CRISPR/Cas-mediated genome editing. This review focuses on insights into RNA Pol III promoters and their types that govern the expression levels of sgRNA in the CRISPR/Cas system. We discussed Pol III promoters structural and functional characteristics and their comparison with Pol II promoters. Further, the use of synthetic promoters to increase the targeting efficiency and overcome the structural, functional, and expressional limitations of RNA Pol III promoters has been discussed. Our review reports various studies that illustrate the use of endogenous U6/U3 promoters for improving editing efficiency in plants and the applicative approach of species-specific RNA pol III promoters for genome editing in model crops like Arabidopsis and tobacco, cereals, legumes, oilseed, and horticultural crops. We further highlight the significance of optimizing these species-specific promoters’ systematic identification and validation for crop improvement and biotic and abiotic stress tolerance through CRISPR/Cas mediated genome editing.